Henry James, Emmanuel Levinas, and the ethics of literature - Pick, A; Pick, Anat (2000)
﻿This study constitutes an attempt to isolate and elucidate the event of personal relations in the later writings of Henry James. I argue that James' singularity rests on his treatment of personal relations in a radical and unfamiliar way. The main goal of this piece is, then, to trace the workings of personal relations, and to understand the peculiar way in which they figure and unfold in the later narratives. By reading James through the ethical philosophy of Emmanuel Levinas, I wish to reconstruct James' major phase as primarily "ethical." Levinasian ethics differs from the branches of moral philosophy in its insistence on the absolute priority and exteriority of the ethical relation between persons: its disengagement from the realms of psychology and consciousness. The ethical relation is envisioned as flourishing precisely in the absence of cognition and thought. Rather than relating to one another as potentially knowable beings, then, persons in James and Levinas relate to one another as mutually unfathomable others. I maintain that this breaching of cognition and knowledge essentially characterizes Jamesian sociality. Read through ethics, as divorced from ideas of consciousness, James' major phase finds its meaning outside the traditional reign of James studies, which takes James as the master of complex elaborations on modes of consciousness. Not consciousness but alterity is James' defining feature, and it is through the readings of alterity that the fundamental event of Jamesian sociality emerges as both primary and unique. "Ethics" thus opens up a new horizon in which the Jamesian is no longer synonymous with consciousness, a horizon which transforms the understanding, not only of James in particular, but of literature in general.